Additions to the moss flora of Peninsular Malaysia - Mohamed, H.; Yong, K.T.; Gunaseelan, G. (Maney Publishing, 2004)
Five new mosses are added to the Peninsular Malaysian moss flora: Gammiella tonkinensis (Broth. & Paris) B.C.Tan, Meiothecium attenuatum Broth., Plagiomnium elimbatum (M.Fleisch.) T.J.Kop., Pohlia flexuosa Hook. and Schoenobryum concavifolium (Griff.) Gangulee. Two moss genera, Pohlia and Schoenobryum and one family Cryphaeaceae are new additions for Peninsular Malaysia. The occurrence of 2-3 abaxial teeth on the leaves of Glyphothecium sciuroides (Hook.) Hampe is reported for the first time.